Pekerja Migran Indonesia dan Potensi Masalah Keluarga yang Ditinggalkan (Family Left-Behind) - Suryadi Suryadi; Kasturi Kasturi; Yusmanto Yusmanto (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
This study aims to determine the potential problems of families left by Indonesian migrant workers. The method used is a literature review as a guide for finding research articles obtained from the internet using the Science Direct, Google Scholar, and Researchgate sites. Details of the article eligibility search strategyusing the PRISMA format (Identification, Screening, Eligibility, Included). Results From the analysis of 10 selected research articles, it shows that the potential problems that can arise as a result of families becoming migrants are: (1) capital management/remittances from work abroad which tend to be used for consumptive purposes; (2) increasing cases of rift in household relations, such as increasing infidelity, even leading to increased divorce and neglect of children; (3) problems with their children's development. Children of migrant workers who are left behind usually have problems in parenting. This can be avoided by implementing four aspects of PMI's family efforts in maintaining family integration, which are a manifestation of the conditions for the family system to run, namely: 1) Continuity of action inÂ changing the division of labor represents adaptation. 2) Cooperation in achieving goals for the decision to become PMI represents goal attainment. 3) Coordination between husband and wife when problems arise represents integration. 4) The suitability of husband and wife actions with a set of values and norms in maintaining family integration represents a latent pattern of maintenance.